Organic co-crystals of 1, 3-bis(4-pyridyl)azulene with a series of hydrogen-bond donors12. Issue 31 (20th July 2018) - Ion, Adrian E.; Dogaru, Andreea; Shova, Sergiu; Madalan, Augustin M.; Akintola, Oluseun; Ionescu, Sorana; Voicescu, Mariana; Nica, Simona; Buchholz, Axel; Plass, Winfried; Andruh, Marius
Abstract : 1, 3-Bis(4-pyridyl)azulene has been employed as a hydrogen bond acceptor to construct two-component organic cocrystals. Abstract : The supramolecular interactions between 1, 3-bis(4-pyridyl)azulene (azbbpy) as a hydrogen bond acceptor and a variety of aromatic hydrogen-bond donors produced new binary molecular co-crystals and a salt. All crystal structures display extensive and very complex hydrogen bond networks containing both homo- and heterosynthons formed through robust O–H⋯N and OH⋯O hydrogen bonds. The binary co-crystals of azbbpy with 4, 4′-biphenol and 4, 4′-oxo-bis-benzoic acid in a 1 : 1 ratio revealed that the recognition process differs. While 4, 4′-biphenol acts both as a donor and an acceptor of protons, generating a two-dimensional supramolecular network in which azbbpy interacts with only one pyridine moiety, the co-crystallization with 4, 4′-oxo-bis-benzoic acid yielded zig-zag chains formed by alternating acid–pyridine supramolecular heterosynthons. Co-crystallization with isophthalic acid yields a 2 : 1 system, 4, as hydrogen-bonded zig-zag supramolecular chains containing a R44(36) graph set organized through strong OH⋯N and weak C–H⋯N hydrogen bonds. Co-crystallization of azbbpy with trimesic acid in different ratios yielded two distinct systems: co-crystal5 and salt6 . In5, the trimesic acid molecules are assembled in supramolecular helical chains which are further connected by azbbpy through hydrogen bonding and π–π interactions into a 3D architecture with channels that host water molecules. A complicated supramolecular 3D architecture is also established between trimesic anions and azbbpyH + cations in crystal6, resulting in channels filled with disordered solvent molecules. These types of interactions were also evidenced in a quantitative way and confirmed on grounds of the Hirshfeld surface mapped with geometrical parameters that characterize close contacts in co-crystals. The optical properties of these supramolecular systems showed strong absorption bands in the visible region due to the azulene fragment.